Perfecting the Administrative Solution to Labour Disputes: Postscript - Joseph, P. (Relations industrielles / Industrial Relations, 1983)
« The judges lack the intimate knowledge of the very dynamic process of industrial relations and collective bargaining. For these reasons...the new labour code has removed the court's jurisdiction over labour disputes...The new law seeks an administrative rather than a judicial solution to labour disputes. »*** JOSEPH, P.A., Faculty of Law, University of Canterbury, New Zealand.** BRITISH COLUMBIA LEGISLATIVE ASSEMBLY DEBATES (1973) (Third Session), at 399-400 per the Hon. W.S. King, Minister of Labour.